Moment computation in shift invariant spaces. (1998) - Eubanks, David A.; van Fleet, Patrick J.; Wang, Jianzhong
Abstract : An algorithm is given for the computation of moments of f ∈ S, where S is either a principal h -shift invariant space or S is a finitely generated h -shift invariant space. An error estimate for the rate of convergence of our scheme is also presented. In so doing, we obtain a result for computing inner products in these spaces. As corollaries, we derive Marsden-type identities for principal h -shift invariant spaces and finitely generated h -shift invariant spaces. Applications to wavelet/multiwavelet spaces are presented.